Lex Cryptographia: Legal Extensions to Smart Contract Breaches and Governance in Blockchain Systems - Annas Rasid Musthafa; Rifda Yussriyyah Putri; Alfaiza Akbar Farizki; Shafanissa Aulya Alma (Jurnal Kajian Pembaruan Hukum, 2024)
The development of smart contract in a decentralized blockchain system raises various problems in the legal field marked by cases of smart contract violations such as the DAO, Parity Wallet, and PlayDapp cases. The breach of smart contract in the blockchain system affects the application and enforcement of conventional law in a virtual world that has no geographical jurisdiction. The limitations of conventional law in regulating the virtual world gave birth to various new legal concepts such as lex cryptographia and virtual state. This research aims to examine the expansion of law in blockchain systems and smart contract, especially in cases of breach of smart contract and the birth of new governance. This research uses doctrinal research methods with a case study approach and literature research. Based on the results of this research, the existence of smart contracts affects the legal expansion of their legitimacy and application as contracts that have legal force. Smart contract that have no ties to territorial jurisdiction give the parties to the smart contract complete freedom to regulate the settlement of contract violations, so that smart contracts become law, legal procedures, and punishment itself in carrying out its functions. In addition, the existence of smart contracts in the blockchain system also gave birth to lex cryptographia as a new law and a blockchain-based virtual state as a new governance model that is not limited by geographical areas.